Levels of heavy metals in deposited dust and soil from selected primary schools in Dar es Salaam - Philip, Joseph Yoeza Naimani; Mkenga, Eliamini Ismail; Othman, Othman Chande (Tanzania Journal of Science, 2018)
The objective of this study was to examine the levels of heavy metals, lead, manganese, nickel, copper, chromium and cadmium in standard one and kindergarten classroom dusts and playing ground soils from selected primary schools along Morogoro road highway (Kimara, Mbezi, Kibamba and Kiluvya primary schools) and away from Morogoro road highway (Makabe, Msumi and Mbopo primary schools) as well as in the Dar es Salaam city center (Uhuru, Mzimuni, Dr. Omari Ali Juma, Manzese and Ubungo National House primary schools), Tanzania. The samples were acid digested and the supernatant analyzed using inductively coupled plasma optical emission spectrometer (ICP-OES). The mean concentrations (mg/kg) range of heavy metals in kindergarten and standard one classroom dust samples were bdl – 3.2 ± 0.2 (Cd), 14.7 ± 0.5 – 30.1 ± 2.2 (Cr), 6701 ± 1201– 277775 ± 32632 (Mn), 5.18 ± 0.59 – 122 ± 145 (Cu), 6.95 ± 1.57 – 30.3 ± 31.1 (Ni) and 17.67 ± 3.56 – 104.9 ± 94.7 (Pb). Similarly, the mean concentrations (mg/kg) range of heavy metals in kindergarten and standard one playing ground soil samples were bdl – 1.86 ± 0.06 (Cd), 5.8 ± 0.8 – 105 ± 124 (Cr), 7176 ± 226 – 191779 ± 82776 (Mn), 1.64 ± 0.01 – 11.51 ± 6.5 (Cu), 1.11 ± 0.2 – 37.5 ± 45.9 (Ni) and 8.9 ± 2.4 – 34.04 ± 1.9 (Pb). The present results, which indicate significantly high levels of heavy metals in school classroom dusts and playing ground soils, signify an important advancement towards shedding light on the alarming threat to school children’s health since classrooms and playing grounds are their immediate environments where they spend significant amount of their early life time.